Stifle anatomic, tomographic and biomechanical features of growing dogs affected by quadriceps contracture. (International Journal of Health, Animal Science and Food Safety, 2018)
Quadriceps contracture is a debilitating and uncommon condition, mostly affecting young dogs. Itcan be congenital or acquired ) and is reported to induce muscular hypotrophy/fibrosis, progressive degenerative joint disease, bone hypoplasia and limb hyperextension. The aim of this study was to elucidate anatomic, tomographic and biomechanical features of stifles affected by quadriceps contracture.Seven 2-month-old dead Dobermann Pinschers with unilateral quadriceps contracture were included. Before gross anatomic evaluation, all stifles underwent Computed Tomography before and after intra-articular administration of iodinated contrast medium. Images were acquired in double positioning (stifle extension and flexion) to identify articular cartilage, Ossification Centres’ (OCs) and menisci abnormalities, which were compared between affected and unaffected limbs. In all affected limbs the stifle was back-turned, the distal femur was extra-rotated and the patella was luxated proximo-medially. Severe lack of physiological stifle movements (rolling, gliding, spinning) was observed, so that affected joints could not be flexed. The articular cartilage of the femur was flattened and irregular in thickness, the femoral trochlea was hypoplasic and sloping, the menisci were misshaped. The OC of the distal femur and proximal tibia were misshaped; the tibial plateau was oriented caudodorsally-cranioventrally and significantly smaller (P
Keywords: Quadriceps contracture; Puppies; Stifle; Skeletal development; Anatomy